Making compact two-lane roundabouts effective for vulnerable road users: an assessment of transport-related externalities - Fernandes, Paulo (2019)
Compact two-lane roundabouts are increasingly popular. Designing cycle lanes at two-lane roundabouts may not benefit motor vehicles, pedestrians and cyclists simultaneously. This study addresses environmental and operational aspects for accommodating bicycle treatments at compact two-lane roundabouts, namely: (i) sharing bicycles with the motor vehicle lanes; (ii) sharing bicycles with pedestrian pathways; (iii) dedicated bicycle lanes separated from pedestrian paths and motor vehicle lanes. Each scenario was subjected to different traffic, pedestrian and cyclist volumes. Using a microscopic traffic model, the operational performance of the above designs was compared. Then, a microscopic emission methodology based on vehicle-specific power and a semi-dynamic model were used to estimate pollutant emissions and traffic noise, respectively. It was found that cyclists travel time increased with the adoption of separated bicycle lanes since this design led to longer paths. However, average intersection travel time, emissions and noise decreased when compared to other design.